Boiling the frog optimally: Nan experiment on survivor curve shapes and internet revenue - Christina Aperjis; Ciril Bosch-Rosa; Daniel Friedman; Bernardo A. Huberman (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
When should a necessary inconvenience be introduced gradually, and when should it be imposed all at once? The question is crucial to web content providers, who in order to generate revenue must sooner or later introduce advertisements, subscription fees, or other inconveniences. Assuming that eventually people fully adapt to changes, the answer depends only on the shape of the "survivor curve" S(x), which represents the fraction of a user population willing to tolerate inconveniences of size x (Aperjis and Huberman 2011). We report a new laboratory experiment that, for the first time, estimates the shape of survivor curves in several different settings. We engage laboratory subjects in a series of six desirable activities, e.g., playing a video game, viewing a chosen video clip, or earning money by answering questions. For each activity we introduce a chosen level x 2 [x min, x max] of a particular inconvenience, and each subject chooses whether to tolerate the inconvenience or to switch to a bland activity for the remaining time. Our key finding is that, in general, the survivor curve is log-convex. Theory suggests therefore that introducing inconveniences all at once will generally be more pro table for web content providers.
Keywords: C91; D40; L11; 330; Internet monetization; online advertising; pricing; reference points; adaptation; laboratory experiment